Triplet State Dynamics in Peridinin-Chlorophyll-a-Protein: A New Pathway of Photoprotection in LHCs? - Alexandre, Maxime T. A. (Biophysical Society, 2007)
This work investigates the interaction of carotenoid and chlorophyll triplet states in the peridinin-chlorophyll-a-protein (PCP) of Amphidinium carterae using step-scan Fourier transform infrared spectroscopy. We identify two carotenoid triplet state lifetimes of ∼13 and ∼42 μs in the spectral region between 1800 and 1100 cm(−1) after excitation of the ‘blue’ and ‘red’ peridinin (Per) conformers and the Q(y) of chlorophyll-a (Chl-a). The fast and slow decaying triplets exhibit different spectral signatures in the carbonyl region. The fast component generated at all excitation wavelengths is from a major conformer with a lactone stretching mode bleach at 1745 cm(−1). One (1720 cm(−1)) and two (1720 cm(−1) and 1741 cm(−1)) different Per conformers are observed for the slow component upon 670- and 530–480-nm excitation, respectively. The above result implies that (3)Per triplets are formed via two different pathways, corroborating and complementing visible triplet-singlet (T-S) spectra (Kleima et al., Biochemistry (2000), 39, 5184). Surprisingly, all difference spectra show that Per and Chl-a modes are simultaneously present during the (3)Per decay, implying significant involvement of (3)Chl-a in the (3)Per state. We suggest that this Per-Chl-a interaction via a delocalized triplet state lowers the (3)Per energy and thus provides a general, photoprotection mechanism for light-harvesting antenna complexes.